Comparison of phenolics, flavonoids and anthocyanin in pigmented and non-pigmented maize in bangladesh - Preety, Israt Jahan; Islam, Ariful; Rahman, Jamilur; Hossain, Ashrafi; Ahmed, Kamal Uddin (Bangladesh Journal of Botany, 2024)
In the present study the compositions of phenolics, flavonoids and anthocyanins in a purple maize (SAU Bhutta 3) variety were determined and compared its phytonutrients with those of other maize varieties cultivated in Bangladesh. The SAU purple maize contained 106.0 ± 8.3 and 165.1 ± 8.0 mg /100 g of methanol soluble and acidic methanol soluble polyphenols, respectively. The SAU Bhutta 3 had the greatest amount of flavonoids (77.0 ± 10.0 mg /100 g) and anthocyanins (69.0 ± 5.0 C3G equv./100 g). Nevertheless, the SAU white maize variety had 31.0 ± 2.0, 47.0 ± 4.4 mg FAE/100 g and 9.0 ± 2.0 mg CE/100 g of free and bound phenolics and total flavonoids, respectively, which were lower than those of the SAU Bhutta 3. Again, the SAU red maize contained the lowest level of total anthocyanin (4.11 ± 1.2 mg C3G/100 g). The SAU Bhutta 3 exhibited higher proportions of insoluble phenolics compared to total phenolics and flavonoids compared to insoluble phenolics. Overall, the SAU Bhutta 3 contained relatively high amounts of phenolics, flavonoids and anthocyanins; thus, this particular maize variety shows significant potential for future utilization. Bangladesh J. Bot. 53(3): 495-502, 2024 (September)